Understanding Of Sufism Hadith In The Tarekat Agung Tulungagung Islamic Boarding School - Nurita, Andris; Sholihin, Muhammad; Shonhaji, Shonhaji; Lutfianto, Mohammad; Faruq, Umarul (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
The current issue is the emergence of subjective interpretations of hadith in the Tarekat Agung Tulungagung Islamic boarding school and the prevalence of mystical teachings among the community. Therefore, this article will examine the interpretation of hadiths related to mu’amalah, worship, and ethics, which are the pillars of the teachings of the tarekat at the Tarekat Agung Tulungagung Islamic Boarding School. The research method used is qualitative. The theories employed in this article are as follows critical history theory, theory of intertextual interpretation and theory of contextual interpretation. Several findings were obtained through data collection techniques such as interviews and observations at the Pondok Pesulukan Tarekat Agung Tulungagung. First, the hadith about mu'amalah narrated by Ibn Shihāb is understood by the mursyids and santris at the Tarekat Agung Tulungagung Islamic boarding school that in joining a tarekat, one must become a person who is useful to others as a means of getting closer to Allah. Second, the hadith about worship narrated by Imam al-Harith is understood that as a salik, one must always worship and devote oneself wholeheartedly to Allah through the guidance of the mursyid. Third, the hadith about morality narrated by Imam Bukhari is understood that a salik must possess three essential moral qualities: morality toward Allah, toward fellow human beings, and toward the entire universe. Thus, the understanding of hadith at the Tarekat Agung Tulungagung Islamic boarding school does not contradict the interpretations of hadith by scholars or academic experts.